Comparison of microbiotic pattern in gastointestinal tract from neonatus born by spontaneous delivery with and without early breastfeeding - Niken Asri Utami, - (Universitas Airlangga, 2012)
Incidence of neonatal death is suppressed about 22% on babies with early breastfeeding in one hour post birth, possibly due to bigger opportunity to get colostrum. Starting at the time the baby was born, the sterile gut will be colonized soon by microbes in several hours. Gestational age, different modes of delivery, and diet are important factors which influence the pattern of microbiota. The aim of this study was to examine the difference of microbiotic pattern in gastrointestinal tract of neonatus born by spontaneous delivery between the ones with and the ones without early breastfeeding. Rectal swab samples were obtained from neonatus born by spontaneous delivery at Dr. Soetomo Hospital with termed gestational age, 30 samples from neonates with early breastfeeding and 30 samples from neonates without early breastfeeding at 2 hours, 12 hours and 24 hours after delivery, and then were tested for the presence of aerobic, anaerobic and microaerophylic microbes with standard methods at Microbiology Laboratory, Dr. Soetomo Hospital, during February –May, 2012. In 2-hour samples significant difference was found in the count of aerobic microbial colony, in which the count in early breastfeeding group was higher than that in non-early breastfeeding group. The microbial types were E. coli, Enterobacter, Staphylococcus epidermidis and Streptococcus faecalis. In 12-hour samples, colony count of Lactobacillus was higher in early breastfeeding group than in non-early breastfeeding group. In 24 hour samples the count of anaerobic microbial colony in non-early breastfeeding group was significantly higher than that in early breastfeeding group, and the bacterial types were Bacteroides, Bifidobacteria and PeptoStreptococcus. In conclusion, early breasfeeding procedure is beneficial in terms of microbiotic pattern, either in types variation and numbers of microbial colony.